1981
DOI: 10.1021/ma50005a015
|View full text |Cite
|
Sign up to set email alerts
|

NMR and ESR study of the conformations and dynamical properties of poly(L-lysine) in aqueous solutions

Abstract: values of ui '+I and li,+l were kept at 3.8 A, and those for d,j+2, dij+3, and dij+, were adjusted by the triangle inequality. In general, the Values ofuij and lij for small lijl have little effect in constraining the conformation of the whole protein.(40) A cutoff distance of 10 A for both the "contact" and "noncontact" distances means that ui, = 10 A and li. = 5 A if d*, < 10 A, and uij = 40 A and I, = 10 A if dei, > 16 A. The triangle inequalities (6) are then applied to every set of three points to modify… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
8
0

Year Published

1986
1986
2014
2014

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 18 publications
(28 reference statements)
1
8
0
Order By: Relevance
“…While the small measure resonant line broadening at high pD indicates some degree of motional restriction upon formation of periodic secondary structure, the magnitude of broadening effects for this small peptide (DP = 16) does not imply substantial aggregation of peptide monomers. Chemical shift values for the random coil (pD 8.6) structure closely match those reported for a similar sample (pD 7, T = 77 °C) of a larger poly( l -lysine) with an average degree of polymerization of 140 units . Very little change in 1 H chemical shift is observed for the high pD samples in Figure B and C. Several factors might account for this.…”
Section: Resultssupporting
confidence: 81%
“…While the small measure resonant line broadening at high pD indicates some degree of motional restriction upon formation of periodic secondary structure, the magnitude of broadening effects for this small peptide (DP = 16) does not imply substantial aggregation of peptide monomers. Chemical shift values for the random coil (pD 8.6) structure closely match those reported for a similar sample (pD 7, T = 77 °C) of a larger poly( l -lysine) with an average degree of polymerization of 140 units . Very little change in 1 H chemical shift is observed for the high pD samples in Figure B and C. Several factors might account for this.…”
Section: Resultssupporting
confidence: 81%
“…At pH 9−11, a transformation to an α-helix is observed by 13 C NMR . Heating the basic solution leads again to the formation of β-pleated sheets, as revealed by ESR and NMR, optical rotatory dispersion measurements, and Raman spectroscopy . IR measurements showed that the secondary structure is also influenced by the chain length. , According to Scheraga, the β-pleated sheet structure is favored by hydrophobic interactions between the side chains by which the entropy of the surrounding water is increased …”
Section: Introductionmentioning
confidence: 98%
“…At pH 9-11 a transformation to a-helices is observed by 13 C NMR. 3 Heating the basic solution leads again to the formation of b-pleated sheets as revealed by ESR and NMR, 4 optical rotatory dispersion measurements 5 and Raman spectroscopy. 6 IR measurements showed that the secondary structure is also influenced by the chain length 7,8 According to Scheraga, the b-pleated sheet structure is favored by hydrophobic interactions between the side chains by which the entropy of the surrounding water is increased.…”
Section: Introductionmentioning
confidence: 99%